Versatility within (4, 4) networks assembled from 1, 4-bis(n-alkyloxy)-2, 5-bis(3, 2′:6′, 3′'-terpyridin-4′-yl)benzene and [Cu(hfacac)2] (Hhfacac = 1, 1, 1, 5, 5, 5-hexafluoropentane-2, 4-dione). (15th September 2022) - Capomolla, Simona S.; Manfroni, Giacomo; Prescimone, Alessandro; Constable, Edwin C.; Housecroft, Catherine E.
Graphical abstract: The coordination behaviour of a series of 1, 4-bis( n -alkyloxy)-2, 5-bis(3, 2′:6′, 3′'-terpyridin-4′-yl)benzene ligands with alkyloxyl substituents ranging from methoxy to n -octyloxy towards [Cu(hfacac)2 ] . H2 O has been investigated. Four structure families have been eludicated including three different variants of a (4, 4) network. Abstract: The reactions of 1, 4-bis( n -alkyloxy)-2, 5-bis(3, 2′:6′, 3′'-terpyridin-4′-yl)benzene ligands with methoxy (1 ), ethoxy (2 ), n -propoxy (3 ), n -butyloxy (4 ), n -pentyloxy (5 ), n -hexyloxy (6 ), n -heptyloxy (7 ) and n -octyloxy (8 ) substituents with [Cu(hfacac)2 ] . H2 O (Hhfacac = 1, 1, 1, 5, 5, 5-hexafluoropentane-2, 4-dione) under conditions of crystal growth by layering have been investigated using different combinations of solvents. The products have been structurally characterized and in all cases, Cu(II) is octahedrally sited in a trans -{Cu(hfacac)2 (N)2 } environment in which N is a pyridine donor in one of the outer rings of a 3, 2′:6′, 3′'-tpy unit. The coordination assemblies fall into four categories. The most populated class consists of (4, 4) nets in which each bis(3, 2′:6′, 3′'-tpy) ligand 1 and 4–8 acts as a 4-connecting node and the Cu(II) centres lie within the plane defined by the nodes; changes in conformation of the 3, 2′:6′, 3′'-tpy units do not affect the assembly of the (4, 4) network. One of two assemblies isolated with ligand 2 is also a (4, 4) net, but powder X-ray diffraction (PXRD) data indicate that this is not representative of the bulk material. [Cu2 (hfacac)4 (3 )] n . 5.5 n C6 H5 Cl exhibits a unique structure consisting of a (4, 4) net with the Cu(II) centres lying above and below the plane of the net. A third class of assembly was found for [Cu3 (hfacac)6 (5 )2 ] n and comprises a (4, 4) net in which half of the ligands are 4-connecting nodes and half coordinate through two pyridine rings and are therefore linkers; the efficient packing in this structure leaves no solvent-accessible voids. A 1D-coordination polymer in which all the bis(3, 2′:6′, 3′'-tpy) ligands are 2-connecting linkers was observed for [Cu2 (hfacac)4 (2 )2 ] n . 1.5 n CHCl3 . 4 n MeOH and PXRD data confirm that the structure is representative of the bulk material. Structural studies have been complemented by thermogravimetic analyses of selected compounds.